Skipping meals and frequency of snack consumption are important eating behaviours related to obesity in hospital employees - Akhlaghi, Masoumeh; Behrouz, Vahideh (Archives of Advances in Biosciences, 2015)
Obesity is an epidemic nutritional disease caused mainly by excessive dietary intake and/or insufficient exercise. The purpose of this study was to investigate associations between a number of demographic characteristics and eating habits with prevalence of overweight and obesity in hospital employees. The study was cross-sectional performed on employees of Namazi Hospital in Shiraz, Iran. Subjects were selected from different departments of the hospital. Demographic characteristics, eating habits, and exercise were questioned by interview. Overweight and obesity was defined as a body mass index ≥ 25 kg/m2. The rate of overweight/obesity was 30.2%. Among demographic characteristics, only age (OR=5.6 for older ages, p=0.001) and sex (OR=0.4 for females, p=0.04) were significantly associated with overweight/obesity. Skipping breakfast was not associated with overweight/obesity, but skipping meals (OR=2.8, p=0.08) and consuming ≥ 3 snacks per day (OR=0.2, p=0.05) had associations with it, although non-significantly. Performing ≥ 60 min/day (but not ≥ 45 min/day) exercise was associated with a lower risk of overweight/obesity (OR=0.1, p=0.01). The association between exercise and overweight/obesity existed in both sexes, but the association between skipping meals and obesity was present only in females (OR=3.8, p=0.05). Females skipped meals especially breakfast more frequently than males (p=0.001) but snack consumption and exercise was not statistically different between the two sexes. Eating 3 meals and at least 3 snacks per day and performing 1 hour or more exercise may be introduced as helpful strategies in prevention of obesity.